Tanzania : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2011)
Tanzania's Second National Strategy for Growth and Reduction of Poverty (NSGRP II) is a continuation of government and national commitments to accelerate economic growth and fight poverty. Though MKUKUTA I (NSGRP I) yielded demonstrable positive results, it failed to meet some targets. MKUKUTA II was therefore implemented for realizing Tanzania's Development Vision 2025 and the Millennium Development Goals (MDGs). MKUKUTA II is oriented more toward growth and enhancement of productivity, with greater alignment of the interventions toward wealth creation as a way out of poverty.